Gondolatok a pécsi tudományegyetem jubileuma kapcsán - Molnár, Dávid (Gerundium, 2019)
Thoughts about the University of Pécs Celebrating it’s 650th Jubilee. The University of Pécs, the first ever university in Hungary, celebrated the 650th anniversary of its establishment in September 2017. The study briefly describes the different projects and events that were initiated in Pécs but also around the country in order to celebrate the jubilee condignly. These efforts included university and department level publications, exhibitions, and other events that attracted attention above and beyond the city of Pécs. It is important to note, that there were a number of international scholars and collaborators involved in the organization of some events.